2022
DOI: 10.3390/ijms23062917
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Crosslinking Polymers Play Major Roles in Improving the Stability and Catalytic Properties of Immobilized Thermomyces lanuginosus Lipase

Abstract: This study aimed to improve the stability and catalytic properties of Thermomyces lanuginosus lipase (TLL) adsorbed on a hydrophobic support. At the optimized conditions (pH 5 and 25 °C without any additions), the Sips isotherm model effectively fitted the equilibrium adsorption data, indicating a monolayer and the homogenous distribution of immobilized lipase molecules. To preserve the high specific activity of adsorbed lipase, the immobilized lipase (IL) with a moderate loading amount (approximately 40% surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…( II ) Representation of lipases immobilized in a hydrophobic surface crosslinked with an ionic polymer. In the presence of surfactant binding points are also lost, however here it is shown that in contrast to I there is no enzymatic desorption [ 161 , 162 ].…”
Section: Figures Schemes and Tablesmentioning
confidence: 96%
See 1 more Smart Citation
“…( II ) Representation of lipases immobilized in a hydrophobic surface crosslinked with an ionic polymer. In the presence of surfactant binding points are also lost, however here it is shown that in contrast to I there is no enzymatic desorption [ 161 , 162 ].…”
Section: Figures Schemes and Tablesmentioning
confidence: 96%
“…However, the possible gain in stability obtained in the derivative through these modifications is not only inevitably accompanied by an increase in the complexity of the immobilization protocol and the reuse of the support, it also involves changes in the activity or selectivity of the derivative, so the modification process should be optimized under those variables in a particular reaction [ 161 ]. This was evidenced in a recent study, in which the authors improved the stability and catalytic properties of Thermomyces lanuginosus lipase (TLL) adsorbed on a hydrophobic support by using additives that function as cross-linking units, allowing the loss of lipase to be reduced from 40% to <2% of the adsorbed enzyme, with only 0.5% w / w of the corresponding additive, further achieving in the case of CS the increase in catalytic efficiency by two-fold [ 162 ]. On the other hand, as an example of the use of these derivatives in API production, the PEI modification of an octyl-agarose derivative of the lipase Eversa ® in the hydrolysis of methyl rac-2-hydroxy-2-phenylacetic acid (also a precursor of cephalosporin, antineoplastics, etc.…”
Section: Immobilization Of Lipasesmentioning
confidence: 99%